2017
DOI: 10.1515/cclm-2016-0576
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs in cardiovascular disease – clinical application

Abstract: microRNAs (miRNAs) are well-known, powerful regulators of gene expression, and their potential to serve as circulating biomarkers is widely accepted. In cardiovascular disease (CVD), numerous studies have suggested miRNAs as strong circulating biomarkers with high diagnostic as well as prognostic power. In coronary artery disease (CAD) and heart failure (HF), miRNAs have been suggested as reliable biomarkers matching up to established protein-based such as cardiac troponins (cT) or natriuretic peptides. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 157 publications
(199 reference statements)
1
73
0
2
Order By: Relevance
“…In cardiovascular diseases, several miRNAs have been suggested as potential biomarkers with high diagnostic and prognostic potential that were comparable to those of established protein-based biomarkers, such as cardiac troponins and natriuretic peptides (22,23). Additionally, miRNAs may also be utilized as therapeutic agents in cardiovascular diseases (24). Recent studies have revealed that circRNAs may function as endogenous miRNA sponges, ultimately exerting a significant effect on downstream miRNA targets.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiovascular diseases, several miRNAs have been suggested as potential biomarkers with high diagnostic and prognostic potential that were comparable to those of established protein-based biomarkers, such as cardiac troponins and natriuretic peptides (22,23). Additionally, miRNAs may also be utilized as therapeutic agents in cardiovascular diseases (24). Recent studies have revealed that circRNAs may function as endogenous miRNA sponges, ultimately exerting a significant effect on downstream miRNA targets.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest that miRNAs are implicated in the development of cardiovascular diseases [16,17]. Among them, many studies have demonstrated that miR-1 plays a critical role in the occurrence of both ventricular and atrial arrhythmias by post-transcriptionally modulating ion channels and proteins related to cardiac electrical activity [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the investigations of the presence and the role of miRNAs in cardiovascular biology and disease have been dramatically expanded. Today the value of post-transcriptional regulation, mediated by miRNAs in cardiovascular homeostasis, in heart disease pathogenesis, diagnosis, and prognosis are well established in the scientific community [124,125] (Table 1).…”
Section: Circulating Mirnas In Cardiovascular Diseasesmentioning
confidence: 99%